Relationship between government spending,gdp and population deflator and employment toward economic growth in Malaysia / Mohd Faris Mohd Yusoff - Mohd Yusoff, Mohd Faris (2011)
Government spending is a provision that the government used to finance government projects, such as administration, defense and public goods provision in order to achieve economic growth. In other words, government spending is a component that contributes to the economic growth in each country. Economic growth can gauge the performance of a country's development, such as increasing total output of goods, infrastructure development, development education and defense. This increase can be seen when the GDP growth in Malaysia recorded an increase of 6.3% in 2007 compared with 5.8% in 2006. This study empirically analyzes the relationship between government spending, population and employment towards economic growth in Malaysia which were measured by Malaysia GDP in 1980 to 2009. Government spending has a strong relationship towards economic growth which it can influences in many ways such as spending for better infrastructure can attract foreigner to invest in Malaysia. This study uses the data from government spending, population, and employment as independent variables. This study will be used simple linear regression by using single regression model and multiple regression analysis to see the relationships between dependent and independent variables